Correction: Detection and characterization of ponatinib reactive metabolites by liquid chromatography tandem mass spectrometry and elucidation of bioactivation pathways. Issue 18 (9th February 2017) - Kadi, Adnan A.; Darwish, Hany W.; Attwa, Mohamed W.; Amer, Sawsan M.
Abstract : Correction for 'Detection and characterization of ponatinib reactive metabolites by liquid chromatography tandem mass spectrometry and elucidation of bioactivation pathways' by Adnan A. Kadi et al., RSC Adv., 2016, 6, 72575–72585.